2002
DOI: 10.1021/bi0268910
|View full text |Cite
|
Sign up to set email alerts
|

Specificity Determinants of Recruitment Peptides Bound to Phospho-CDK2/Cyclin A,

Abstract: Progression through S phase of the eukaryotic cell cycle is regulated by the action of the cyclin dependent protein kinase 2 (CDK2) in association with cyclin A. CDK2/cyclin A phosphorylates numerous substrates. Substrate specificity often employs a dual recognition strategy in which the sequence flanking the phospho-acceptor site (Ser.Pro.X.Arg/Lys) is recognized by CDK2, while the cyclin A component of the complex contains a hydrophobic site that binds Arg/Lys.X.Leu ("RXL" or "KXL") substrate recruitment mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
178
5
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(192 citation statements)
references
References 46 publications
8
178
5
1
Order By: Relevance
“…Several conserved residues are on the surface of the α1 helix in a position accessible for interactions with substrates and regulators of the cyclin A-Cdk complexes (29)(30)(31). Therefore, point mutations were generated to determine whether these residues are important for cyclin A CLS functions.…”
Section: Resultsmentioning
confidence: 99%
“…Several conserved residues are on the surface of the α1 helix in a position accessible for interactions with substrates and regulators of the cyclin A-Cdk complexes (29)(30)(31). Therefore, point mutations were generated to determine whether these residues are important for cyclin A CLS functions.…”
Section: Resultsmentioning
confidence: 99%
“…The p300 transcriptional co-activator acetylates pRb on the adjacent lysine residues K873/K874 (Chan et al, 2001a), and acetylation is enhanced by the viral oncoprotein E1A, which recruits p300 and pRb into a multimeric protein complex. Acetylation of pRb impedes the phosphorylation of pRb by cyclin/Cdk complexes, which is perhaps not entirely unexpected as the site of acetylation falls within the motif believed to be required for binding Cdks (residues 868-878) (Adams et al, 1999;Lowe et al, 2002). Acetylation of pRb at K873/K874 is under cell cycle control and increased levels of acetylation occur during S phase (Chan et al, 2001a).…”
Section: Acetylation Of Prbmentioning
confidence: 90%
“…A structural study examining the association between pRb and PP1 revealed an enzyme docking site in the Cterminal domain of pRb that is essential for PP1 activity towards pRb (Hirschi et al, 2010). The phosphatase binding site maps to amino acid residues 870-882, which overlaps with a well-documented Cdk binding site (amino acid 868-878) (Schulman et al, 1998;Adams et al, 1999;Lowe et al, 2002). PP1 competes with Cdkcyclins for pRb binding, maintains pRb in an active growth-suppressing form and blocks cell cycle progression (Hirschi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This crystal structure solved at 2.24 Å resolution contains several important elements. 30 The foundation is formed by a complex of two proteins, cyclin A and phosphorylated cyclin-dependent protein kinase 2 (pCDK2), of which there are two copies in the crystallographic asymmetric unit. A p53 CTD 9-mer fragment (residues 378-386) is bound to one of the cyclin A chains.…”
Section: Pdb File Preparationmentioning
confidence: 99%